Assessing Logistics Service Quality in Omni-Channel Retailing Through Integrated SERVQUAL and Kano Model - Lanhui Cai; Yanfeng Liu; Po-Lin Lai; Xiaonan Zhu; Kum Fai Yuen; Xueqin Wang (Systems)
Omni-channel retailing is a novel form that combines online, offline, and mobile channels to provide consumers with a seamless shopping experience. Nevertheless, the implementation of omni-channel retailing necessitates effective logistics support. Hence, the quality of logistics services is critical for omni-channel retailing services. This research aims to investigate logistics service quality (LSQ) and its impact on consumer satisfaction by combining the decomposed SERVQUAL framework, Kano model and hierarchical regression analysis. A total of 460 valid responses were obtained. Building upon the SERVQUAL framework, this study presents a comprehensive framework for evaluating omni-channel retail logistics service quality. Using the Kano model, 11 logistics service quality attributes were categorised into three categories: must-be, one-dimensional, and attractive, based on their respective impact on satisfaction. The results of the hierarchical regression analysis confirm that the attributes belonging to the must-be category exert the most significant influence on satisfaction. The findings add to theoretical studies of omni-channel retailing LSQ and provide insights for omni-channel retailers and logistics service providers.